Dignity and human rights-based care and support for older persons - Carlos Augusto de Mendonça Lima; Kiran Rabheru (Academia Mental Health & Well-Being)
The global increase in the older population has led to a rise in mental health conditions and psychosocial disabilities, both in absolute numbers and as a percentage of aging cohorts. This demographic shift increases the risk of human rights violations driven by ageism, mentalism, and ableism. However, older persons often face unique challenges in exercising their rights due to variations in autonomy, cognitive function, and care needs. A human rights-based approach to mental health care must explicitly address these nuances. This paper examines how dignity—a fundamental human right—can be meaningfully operationalized in care models. We propose a structured, evidence-based approach to care that is grounded in dignity, human rights, and the principles of the UN Decade of Healthy Ageing. This framework also emphasizes trauma-sensitive care, recognizing the vulnerabilities of older persons in institutional settings.